Dietary nitrogen alters codon bias and genome composition in parasitic microorganisms. Issue 1 (December 2016) - Seward, Emily; Kelly, Steven
Abstract Background Genomes are composed of long strings of nucleotide monomers (A, C, G and T) that are either scavenged from the organism's environment or built from metabolic precursors. The biosynthesis of each nucleotide differs in atomic requirements with different nucleotides requiring different quantities of nitrogen atoms. However, the impact of the relative availability of dietary nitrogen on genome composition and codon bias is poorly understood. Results Here we show that differential nitrogen availability, due to differences in environment and dietary inputs, is a major determinant of genome nucleotide composition and synonymous codon use in both bacterial and eukaryotic microorganisms. Specifically, low nitrogen availability species use nucleotides that require fewer nitrogen atoms to encode the same genes compared to high nitrogen availability species. Furthermore, we provide a novel selection-mutation framework for the evaluation of the impact of metabolism on gene sequence evolution and show that it is possible to predict the metabolic inputs of related organisms from an analysis of the raw nucleotide sequence of their genes. Conclusions Taken together, these results reveal a previously hidden relationship between cellular metabolism and genome evolution and provide new insight into how genome sequence evolution can be influenced by adaptation to different diets and environments.